2019
DOI: 10.1590/0102-311x00091018
|View full text |Cite
|
Sign up to set email alerts
|

Comportamentos em saúde e o controle da hipertensão arterial: resultados do ELSI-BRASIL

Abstract: Resumo: O objetivo foi quantificar a contribuição de comportamentos em saúde selecionados para a prevalência do controle da hipertensão junto a adultos brasileiros com 50 ou mais anos de idade. Foram analisados os dados do ELSI-Brasil. Foram incluídos, no estudo, 4.318 indivíduos com 50 anos ou mais, que relataram ter recebido diagnóstico médico de hipertensão arterial e faziam tratamento medicamentoso para ela. Os comportamentos em saúde selecionados foram: prática de atividade física, adoção de dieta saudáve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 30 publications
0
3
0
19
Order By: Relevance
“…The relationship between males and uncontrolled BP shows similar results to those of Sousa et al 25 . On the other hand, other authors found no differences between genders 26 . Although not fully understood, sex can affect both the prevalence and the rate of hypertension control 27 .…”
Section: Discussionmentioning
confidence: 78%
“…The relationship between males and uncontrolled BP shows similar results to those of Sousa et al 25 . On the other hand, other authors found no differences between genders 26 . Although not fully understood, sex can affect both the prevalence and the rate of hypertension control 27 .…”
Section: Discussionmentioning
confidence: 78%
“…Both countries face great challenges in terms of aging and health. In both, an increasing number of older people suffer from multiple chronic conditions, such as cardiovascular and cerebrovascular diseases, systemic arterial hypertension, rheumatic diseases, obesity and diabetes (26,39,(47)(48)(49)(50)(51).…”
Section: Introductionmentioning
confidence: 99%
“…Os hábitos e comportamentos relacionados à saúde do homem são culturalmente mediados, tomam também formas bastante pessoais influenciado por valores, crenças e condições sociais (7) . É nesta dimensão que se encontram, provavelmente, as maiores lacunas do fazer da saúde pública para homens, ao não levar em conta o caráter das escolhas de comportamento, especialmente quando se trata da promoção da saúde e do cuidar de homem.…”
Section: Introductionunclassified